2017
DOI: 10.1038/modpathol.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p16/Ki-67 dual-stained cytology as triage test for high-risk human papillomavirus-positive women

Abstract: The aim of this study was to evaluate the clinical utility of p16/Ki-67 dual staining, for the identification of CIN in high-risk HPV-positive women from a non-responder screening cohort. P16/Ki-67 dual staining, Pap cytology, and HPV16/18 genotyping were performed on physician-taken liquid-based samples from 495 women who tested high-risk HPV positive on self-sampled material (PROHTECT-3B study). Different triage strategies involving p16/Ki-67 dual staining were evaluated for sensitivity, specificity, and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 42 publications
8
53
3
1
Order By: Relevance
“…14 Several studies have shown increased sensitivity and specificity for cervical cancer screening using p16 staining in conjunction with other biomarkers, such as p16/Ki-67 15,16,[24][25][26] and Survivin, the inhibitor of apoptosis. 27 …”
Section: ■Discussionmentioning
confidence: 99%
“…14 Several studies have shown increased sensitivity and specificity for cervical cancer screening using p16 staining in conjunction with other biomarkers, such as p16/Ki-67 15,16,[24][25][26] and Survivin, the inhibitor of apoptosis. 27 …”
Section: ■Discussionmentioning
confidence: 99%
“…21 In ATHENA, and other studies, DS testing demonstrated better performance (improved sensitivity and at least equal specificity) compared to cytology for the cross-sectional detection of ≥CIN3 in hrHPV-positive women. 20,[22][23][24][25][26][27][28][29][30][31] However, like Pap cytology, DS testing is not integrated into the first-line HPV screening test, and both Pap cytology and DS testing require the preparation of a slide for subjective microscopic assessment by highly trained professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The E7 oncoprotein disrupts the pRb/E2F suppressor complex, thus leading to the release of the E2F transcriptional factor which subsequently stimulates the transition of cell cycle from G1 to S phase . Furthermore, the E7‐mediated degradation of pRb triggers the overexpression of the nuclear protein p16 . In particular, inactivation of pRb inhibits the negative feedback control of p16 and subsequently leads to the excessive expression of p16 in order to eliminate the prolonged proliferation of HPV infected cells …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the E7‐mediated degradation of pRb triggers the overexpression of the nuclear protein p16 . In particular, inactivation of pRb inhibits the negative feedback control of p16 and subsequently leads to the excessive expression of p16 in order to eliminate the prolonged proliferation of HPV infected cells …”
Section: Introductionmentioning
confidence: 99%